2021
DOI: 10.36953/ecj.2021.221218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofertilizers and phosphorus on growth parameters and yield of Cowpea (Vigna unguiculata (L.) Walp.) in sandy loam soil of Prayagraj

Abstract: A field experiment was carried out during Kharif, 2020 at Crop Research Farm, Department of Agronomy, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj (U.P) on sandy loam soil to assess the effect of biofertilizers and phosphorus on growth parameters and yield of Cowpea. The design of field experiment was Randomized block design consisting of ten treatments each replicated thrice. Experimental results showed significant increase in growth parameter viz., Plant height (81.09 cm), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
3
3
0
Order By: Relevance
“…Further significant and maximum dry weight was recorded with the application of 70 kg/ha P₂O₅ which could be attributable to the favourable effect of phosphorus application on root growth and phosphorus availability which results in more root surface for bacterial infection and improved biological nitrogen fixation which helps in better dry matter production. Similar results were also reported by Jayshree and Umesha [11].…”
Section: Plant Dry Weightsupporting
confidence: 92%
See 1 more Smart Citation
“…Further significant and maximum dry weight was recorded with the application of 70 kg/ha P₂O₅ which could be attributable to the favourable effect of phosphorus application on root growth and phosphorus availability which results in more root surface for bacterial infection and improved biological nitrogen fixation which helps in better dry matter production. Similar results were also reported by Jayshree and Umesha [11].…”
Section: Plant Dry Weightsupporting
confidence: 92%
“…However, the treatment 8 (PSB + Rhizobium + 60 kg/ha P₂O₅) was found to be statistically at par with treatment 9 (PSB + Rhizobium + 70 kg/ha P₂O₅) in Table 1.Significant and higher crop growth rate was recorded with the application of PSB along with Rhizobium which might be due to better accumulation of dry matter throughout the plant's vegetative and reproductive phase that enhances the physiological and metabolic activity and growth by assimilating the available nutrients at exponential rate and ease more photosynthesis, which results into higher crop growth rate. Similar results were also reported by Jayshree and Umesha [11].…”
Section: Crop Growth Rate (G/m 2 /Day)supporting
confidence: 92%
“…The results in a table (3) indicated that there are significant differences between the two cowpea cultivars, V1 cultivar excelled in the characteristics of number of branches (8.87 branch plant -1 ), number of leaves (34.6 leaf plant -1 ), number of pods (120.44 pods plant -1 ) and seed yield (1859.5 kg ha -1 ) compared to V 2 cultivar recorded the lowest average for these traits in the number of branches (7.44 branch plant -1 ), number of leaves (31.4 leaf plant -1 ), number of pods (114.73 pods plant -1 ) and seed yield (1568.4 kg ha -1 ). The reason for variation may be attributed to the genetic factor which affects the increase in number of branches per plant and number of leaves per plant leading to an increase in the number of pods and seed yield, as well as the ability of the variety to benefit from light, water and other factors in the formation of the largest growth [9], and increase of leaves number which reflected in an increase of the efficiency of the photosynthesis process and the ability of the cultivar to increase the formation of fruit buds and the number of pods [10], and reflected on seed yield [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…The plant yield effect by the additions of bio-fertilizer. [3] has found that the seed yield increased with the addition of bio-fertilizer with different concentrations of chemical fertilizer. Rather, reducing chemical fertilizer with bio-fertilizer gave the highest yield of the treatment 45 kg chemical + biological ( 2.06 tons ha -1 ) While 55 kg chemical + biological treatment gave a seed yield of 1.84 tons ha -1 compared to the control treatment (1.34 tons ha -1 ), the study shows the role of biological fertilizer in increasing the yield and reducing the proportion of chemical fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…The highest was recorded at T 16 which was at par with 40 kg P 2 O 5 ha -1 + Rhizobium + PSB (T 12 ). This increased in plant height might be due to the involvement of P in the rhizosphere environment and plant system by enhancing the photosynthetic activity and plant metabolism thereby improving the plant growth and its development [26] and due to the synergistic effect between phosphorus and biofertilizers converting the insoluble phosphates into soluble form for plant absorption [27].…”
Section: Plant Heightmentioning
confidence: 99%